LOR: AMALGAMATING THAI DANCE AND WESTERN DRAMA FOR CONSTRUCTING IDENTITY OF THAI MODERN DRAMA - Sukee, Punnasak; Vudhaditya, Vijjuta (Fine Arts Journal: Srinakharinwirot University, 2020)
This research aims to investigate the concepts and creative process of a Thai modern play, “LOR: Love, Obsession, Revenge”, which was the project to be performed in Canada. The study was conducted by analyzing the creative process which employed and applied the western methods of acting, directing, and playwriting to Thai play based on the ancient Thai literature, “Lilit Phra Lor”. The findings revealed that Thai play with Thai identity could effectively communicate the following 4 steps of Creative Process to foreigners. The first step is Pre-production Process, which consists of constructing a universal theme in Thainess, the interpretation of traditional literature, the playwriting in accordance with Aristotle’s Poetics theory, the genre classification of the tragedy, and the presentation in theatrical style and form. The second step is Production Process, which consists of rehearsal procedures using Stanislavski’s legendary method that emphasizes the naturalistic or realistic inside the actors as well as the directing techniques that focuses on expressing the personal identity of the director through ideas and stage production. The third step is about Performance, which was performed on 28th July 2015 at Fei & Milton Wong Experimental Theatre, Vancouver, Canada. The majority of the audiences were foreigners. The show created sense of involvement in audiences and the universal theme made the play comprehensible. The audiences recognized “Thainess” from both form and content of the play. The subtitle was provided to the audiences as the tool for better understanding. The fourth step is Post-production Process. The organizers and sponsors were satisfied with the results of this project, as it promoted the ability of modern Thai theatre artists and Thai modern drama.